Kluyveromyces fragilis RNA extract supplementation promotes growth, modulates stress and inflammatory response in zebrafish. (23rd January 2018) - Falcinelli, Silvia; Randazzo, Basilio; Vargas Abúndez, Jorge A; Cangiotti, Gaia; Olivotto, Ike; Carnevali, Oliana
Abstract: Due to the undesirable consequences associated with antibiotics use, researchers and food producers have studied alternative feeding, for the control of fish diseases and animal welfare improvement. However, the beneficial properties of RNA yeasts extract in aquaculture have been barely considered. The present study investigated the beneficial properties of RNA yeast extract from Kluyveromyces fragilis on survival rate, weight and length as well as on molecular pathways involved in growth, immuno‐system and oxidative stress using zebrafish ( Danio rerio ) as an experimental model. The yeast extract has been administrated to zebrafish at three different concentrations (60–180–300 ppm) via zooplankton ( Artemia salina ) for 21 days. Results highlighted yeast extract RNA capability to enhance growth and to improve larvae survival rate in a dose‐dependent manner. In fact, gene expression data showed the ability of the RNA yeast extract to up‐regulate genes involved in growth and to restore stress‐related condition due to the early larval development coupled with the RNA yeast extract administration. In addition, gene expression showed that RNA yeast extract acts as inflammatory‐reducer, but did not enhance the immune response. Histological analysis showed that all three treated groups displayed a thicker gut epithelium, higher intestinal crypts coupled with higher enterocytes lengths compared to control group. In conclusion, these findings provide a large gene network through which yeast RNA extract acts and, by inducing transcriptional changes, modulate the physiological control of growth and inflammatory response coupled with the increase in length and dry weight, together with a higher survival ratio and an intestinal architecture amelioration.